Differences in Nicotine Encoding Dopamine Release between the Striatum and Shell Portion of the Nucleus Accumbens. Issue 3 (March 2019) - Chen, Yuan-Hao; Lin, Bon-Jour; Hsieh, Tsung-Hsun; Kuo, Tung-Tai; Miller, Jonathan; Chou, Yu-Ching; Huang, Eagle Yi-Kung; Hoffer, Barry J.
The aim of this work was to determine the effect of nicotine desensitization on dopamine (DA) release in the dorsal striatum and shell of the nucleus accumbens (NAc) from brain slices. In vitro fast-scan cyclic voltammetry analysis was used to evaluate dopamine release in the dorsal striatum and the NAc shell of Sprague–Dawley rats after infusion of nicotine, a nicotinic acetylcholine receptor (nAChR) antagonist mecamylamine (Mec), and an α4β2 cholinergic receptor antagonist (DHβe). DA release related to nicotine desensitization in the striatum and NAc shell was compared. In both structures, tonic release was suppressed by inhibition of the nicotine receptor (via Mec) and the α4β2 receptor (via DHβe). Paired-pulse ratio (PPR) was facilitated in both structures after nicotine and Mec infusion, and this facilitation was suppressed by increasing the stimulation interval. After variable frequency stimulation (simulating phasic burst), nicotine infusion induced significant augmentation of DA release in the striatum that was not seen in the absence of nicotine. In contrast, nicotine reduced phasic DA release in NAc, although frequency augmentation was seen both with and without nicotine. Evaluation of DA release evoked by various trains (high-frequency stimulation (HFS) 100 Hz) of high-frequency stimulation revealed significant enhancement after a train of three or more pulses in the striatum and NAc. The concentration differences between tonic and phasic release related to nicotine desensitization were more pronounced in the NAc shell. Nicotine desensitization is associated with suppression of tonic release of DA in both the striatum and NAc shell that may occur via the α4β2 subtype of nAChR, whereas phasic frequency-dependent augmentation and HFS-related gating release is more pronounced in the striatum than in the NAc shell. Differences between phasic and tonic release associated with nicotine desensitization may underlie processing of reward signals in the NAc shell, and this may have major implications for addictive behavior.